Solutions for a modern city : Arup in Beijing. - Arup Associates (London : Black Dog, 2008)
"Founded in 1946 by Sir Ove Nyquist Arup and with offices in 37 countries worldwide, Arup has become one of the most progressive creative forces behind many of today's most innovative designs in the built environment, including the Sydney Opera House, the Centre Pompidou in Paris, London's 'Gherkin' and Millennium Bridge and the Manchester Aquatic Centre." "Solutions for a Modern City: Arup in Beijing explores the major projects undertaken in Beijing by this influential firm of designers, engineers, planners and business consultants. With China's economic growth and rise in population, their holding of the Olympics and investment in the projects has had a significant impact on Beijing and the wider country as a whole. Following Beijing's appointment as host city for the 2008 Olympic Games, Arup has had a significant influence on the astonishing architectural development occurring in Beijing - and across China."--BOOK JACKET.
Foreword / Terry Hill and Andrew Chan -- Solutions for a Modern City / Steve Rose -- The Art of Aesthetic Engineering / Dan Hewitt -- Project Beijing: Time, Scale, Transformation / Vesna Petresin Robert -- Arup in Beijing -- The Arup Story -- National Stadium -- National Aquatics Center -- Beijing Parkview Green -- Fencing Hall / National Convention Center -- Beijing Capital International Airport Terminal 3 -- China Central Television's Headquarters -- Nokia Green Building -- China World Trade Center Phase 3 -- Beijing South Rail Station -- GreenPixZero Energy Media Wall --Acknowledgements -- Credits <U+2013> Colophon.
Formerly CIP.
Includes bibliographical references.
Text in English with a foreword and acknowledgements in Chinese.
Keywords: Arup Associates -- Catalogues; Arup Associates; Ove Arup and Partners; Arup Associates; Architecture -- Chine -- Pékin.; Architecture; Buildings; Architektur; Architecture -- China -- Beijing; China -- Beijing; Peking; Pékin (Chine) -- Constructions; Beijing (China) -- Buildings, structures, etc